Effects of a physical activity programme to prevent physical performance decline in onco‐geriatric patients: a randomized multicentre trial. Issue 2 (4th March 2019) - Arrieta, Haritz; Astrugue, Cyril; Regueme, Sophie; Durrieu, Jessica; Maillard, Aline; Rieger, Alban; Terrebonne, Eric; Laurent, Christophe; Maget, Brigitte; Servent, Véronique; Lavau‐Denès, Sandrine; Dauba, Jérôme; et al.
Abstract: Background: Older adults with cancer experience negative long‐term functional effects of both cancer and treatments. Exercise may minimize their age‐related and cancer‐related functional decline. Methods: We conducted a multicentre open‐label 12 month randomized clinical trial with two parallel arms including participants aged ≥70 years with lymphoma or carcinoma requiring curative treatment. The study started at the beginning of any phase of cancer treatment (surgery, chemotherapy, or radiotherapy). The usual care group (UCG) received the current national recommendations in physical activity (a guideline without specific counselling). The intervention group (IG) received 1 year phoned physical activity advice individually adapted to physical assessment (twice a month during the first 6 months and then monthly). The primary outcome was the proportion of subjects with a 1 year decreased short physical performance battery (SPPB) score of 1 point or more. Physical, cognitive, and clinical secondary outcomes were also investigated. Results: We allocated 301 participants (age 76.7 ± 5.0, female 60.6%) to each group. At baseline, the median SPPB was 10/12 in both groups. Breast was the most frequent tumour site (35.7%). After 1 year, 14.0% of participants in the UCG and 18.7% in the IG had a decrease in SPPB score of 1 point or more ( P = 0.772). At 2 years, there was no difference in SPPB, gait speed, International Physical Activity Questionnaire score, and verbal fluency. Subgroup analyses after 2 years showed a decline in SPPB for 29.8% of UCG and 5.0% of IG breast cancer participants ( P = 0.006), in 21.7% of UCG and 6.2% of IG female participants ( P = 0.019), and in 24.5% of UCG and 11.1% of IG normal nutritional status participants ( P = 0.009). Falls, hospitalization, institutionalization, and death rates were similar in both groups. Conclusions: Personalized phoned physical activity advice had not reduced functional decline at 1 year but provided preliminary evidence that may prevent physical performance decline at 2 years in older adults with breast cancer.